Selecting working fluids in an organic rankine cycle for power generation from low temperature heat sources (2014)
This paper presents a thermodynamic study carried out on the use of low-temperature heat sources for power generation through a subcritical Rankine cycle with organic working fluids. An analysis of the state of the art of this technology shows the selection of the working fluid as an open research line, since until now there is no fluid that can meet all environmental and technical aspects to be considered in these cycles. Hence, we have developed a series of simulations that allow us to study the behavior of the Rankine cycle with different configurations and fluids (wet, dry and isentropic) which has led us to observe the influence on the overall cycle efficiency when we change the type of fluids used (refrigerants, hydrocarbons and water) as well as the conditions of temperature, pressure, flow, etc. With the work realized, the viability of this type of processes is demonstrated for the recovery of heat in industry and/or the use of renewable sources of low and medium temperature for the production of electricity.